The Accuracy of Urinary TIMP-2 and IGFBP7 for the Diagnosis of Cardiac Surgery-Associated Acute Kidney Injury: A Systematic Review and Meta-Analysis. (October 2020) - Tai, Qiang; Yi, Huimin; Wei, Xuxia; Xie, Wenfeng; Zeng, Ou; Zheng, Donghua; Sun, Jiaqi; Wang, Ganping; Wang, Siqi; Liu, Genglong
Background: Tissue inhibitor of metalloproteinase 2 (TIMP-2) and insulin-like growth factor binding protein 7 (IGFBP7) are recent promising markers for identification of cardiac surgery-associated acute kidney injury (CSA-AKI). The aim of this study was systematically and quantitatively to evaluate the accuracy of urinary TIMP-2 and IGFBP7 for the diagnosis of CSA-AKI. Methods: Three databases including PubMed, ISI web of knowledge, and Embase were systematically searched from inception to March 2018. Two investigators conducted the processes of literature search study selection, data extraction, and quality evaluation independently. Meta-DiSc and STATA were used for all statistical analyses. Results: A total of 8 studies comprising 552 patients were included in this meta-analysis. Pooled sensitivity and specificity with corresponding 95% confidence intervals (CIs) were 0.79 (95% CI, 0.71-0.86, I 2 = 74.2%) and 0.76 (95% CI, 0.72-0.80, I 2 = 80.8%), respectively. Pooled positive likelihood ratio (LR), negative LR, and diagnostic odds ratio were 3.49 (95% CI, 2.44-5.00, I 2 = 61.5%), 0.31(95% CI, 0.19-0.51, I 2 = 51.8%), and 14.89 (95% CI, 7.31-30.32, I 2 = 27.9%), respectively. The area under curve estimated by summary receiver operating characteristic was 0.868 (standard error [SE] 0.032) with a Q* value of 0.799 (SE 0.032). Sensitivity analysis demonstrated that one study notably affected the stability of pooled results. One of the subgroups investigated—AKI threshold—could account for partial heterogeneity. Conclusion: Urinary TIMP-2 and IGFBP7 is a helpful biomarker for early diagnosis of CSA-AKI. And, the potential of this biomarker with a broader spectrum of clinical settings may be the focus of future studies.